KENDALI MUTU BRANDING SEKOLAH INSPIRATIF: UPAYA SD MUHAMMADIYAH 15 SURABAYA (LIMAS) DALAM MENINGKATKAN KUALITAS SISWA MENUJU SUMBER DAYA MANUSIA MADANI: Penelitian Kualitatif Studi Kasus - Afis, Muhammad Nabil; Vidiyanti; Marwan Supriyanto; Fine Heliyani; Anandhita Stefhanie; Aliet Noorhayati Sutisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discussed the efforts of SD Muhammadiyah 15 Surabaya (SD Limas) in improving the quality of Human Resources (HR) through an inspirational school branding strategy. With a qualitative research method and a case study approach, this research reviews the transformation of Limas Elementary School in creating an educational environment that supports the development of student character and achievements. Data was collected through observation, interviews, and documentation during the Field Work Lecture (KKL) activities carried out by students of the University of Muhammadiyah Cirebon on January 20-22, 2025. The results showed that the inspirational innovative program was applied, such as One Day Inspiration, I Love The Quran, and Summer Camp Study, positive impact on academic and non-academic improvements. In addition, inspiring school environments and superior programs such as the Koran Tahfidz, Qiroatil Qu'ran Standardization, Children Class Skill, Limas Course, and Limas Care contribute to forming competitive madani human resources nationally and globally. This study refers to the effort to improve school human resources through inspirational school branding strategies.